2004
DOI: 10.1007/s00134-004-2311-8
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of patients with severe acute respiratory syndrome in a chest ward in southern Taiwan

Abstract: Old age, high white blood cell counts, high peak grade fever, and close or prolonged contact with a SARS patient increase the risk of intubation in previous healthy SARS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 10 publications
5
24
0
Order By: Relevance
“…Based on the BNHI policy requiring quality of care for PMV patients, the total numbers of PMV patients has not increased, but the total population of Taiwan increased. 18 Our study also showed a significant decrease in the prevalence of PMV in older patients (ie, PMV patients age 75 years or older decreased from 74% in 2004 to 68% in 2007, but the number of comorbidities also increased from 2004 to 2007 during the same period). Duration of ventilation is reportedly associated with cause of ICU admission, age, and treatment location.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Based on the BNHI policy requiring quality of care for PMV patients, the total numbers of PMV patients has not increased, but the total population of Taiwan increased. 18 Our study also showed a significant decrease in the prevalence of PMV in older patients (ie, PMV patients age 75 years or older decreased from 74% in 2004 to 68% in 2007, but the number of comorbidities also increased from 2004 to 2007 during the same period). Duration of ventilation is reportedly associated with cause of ICU admission, age, and treatment location.…”
Section: Discussionsupporting
confidence: 65%
“…The 2000 BNHI policy for PMV patients apparently decreased the stay of PMV patients. 18 The decrease in stay was larger in regional hospitals and district hospitals, as compared to medical centers, and most patients had initiated mechanical ventilation in the ICUs of short-term acute care medical centers. Patients with underlying chronic cardiorespiratory illnesses tended to remain ventilator-dependent and tended to transition from acute illness status to chronic or critical illness status.…”
Section: Discussionmentioning
confidence: 99%
“…However, few articles were written describing the clinical characteristics and management of SARS patients in Taiwan. [4][5][6][7][8] This study delineates clinical features, laboratory data, chest radiography, management and outcomes for patients with probable SARS at a SARS center in Taipei, and determines factors associated with respiratory failure and subsequent intubation in such patients.…”
Section: Study Populationmentioning
confidence: 99%
“…Among these SARS patients, 16 were previously healthy hospital workers, 1 of which died during hospitalization [5]. The remaining 15 patients survived SARS and all were eligible for enrolment in this study.…”
Section: Methodsmentioning
confidence: 99%
“…This outbreak occurred in the chest wards where 44 subjects had contracted the disease, including 16 previously healthy medical personnel [5]. Recovered hospital workers resumed regular daily activities without significant symptoms after hospital discharge.…”
Section: Introductionmentioning
confidence: 99%